Review of Design Elements within Power Infrastructure Cyber–Physical Test Beds as Threat Analysis Environments - Bjorn Vaagensmith; Vivek Kumar Singh; Robert Ivans; Daniel L. Marino; Chathurika S. Wickramasinghe; Jacob Lehmer; Tyler Phillips; Craig Rieger; Milos Manic (Energies, 2021)
Cyber–physical systems (CPSs) are an integral part of modern society; thus, enhancing these systems’ reliability and resilience is paramount. Cyber–physical testbeds (CPTs) are a safe way to test and explore the interplay between the cyber and physical domains and to cost-effectively enhance the reliability and resilience of CPSs. Here a review of CPT elements, broken down into physical components (simulators, emulators, and physical hardware), soft components (communication protocols, network timing protocols), and user interfaces (visualization-dashboard design considerations) is presented. Various methods used to validate CPS performance are reviewed and evaluated for potential applications in CPT performance validation. Last, initial simulated results for a CPT design, based on the IEEE 33 bus system, are presented, along with a brief discussion on how model-based testing and fault–injection-based testing (using scaling and ramp-type attacks) may be used to help validate CPT performance.